The harmonization of the tax system of the Republic of Kazakhstan, in terms of accession to the World Trade Organization and the Customs Union - Balabekova, K A. (Journal of Economic Research & Business Administration, 2015)
This article deals with the causes of economic unions , are examples of such economic relations, their advantages, disadvantages and therefore the occurrence of natural causes creation of a new economic space , free from customs duties. It further states that the expanded boundaries of the market for entrepreneurs in the face of new customers , leads to an increase in business activity. And the appearance on the market of similar goods and services impliesincreased competition . Here , taxes can act governing instrument of the economy , encouraging the priority sectors of the economy and eliminating loss-making enterprises . Accordingly, it is neglected by the fact that the establishment of economic unions and free boundaries of business , you need to remember about the difference between the tax systems of the member states of these unions , and thus to harmonize them , in order to avoid double taxation.It then identifies the main stages of the harmonization of tax systems in the customs union , the problems faced by the member countries of the Customs Union , as well as their legislative solutions . The article also provided comparisons of tax rates of the participants in the economic union, as well as the rating of doing business in these countries.